Cocoanut [sic] Palms, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
A picture of a coconut grove near the sea shore with two women in traditional dress standing on a hill near the grove.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Plantations--Trinidad and Tobago; Women--Trinidad and Tobago